EARLY PRECAMBRIAN CRUSTAL EVOLUTION OF THE BELOMORIAN AND TRANS-NORTH CHINA OROGENS AND SUPERCONTINENTS RECONSTRUCTION - A. I. Slabunov; Jinghui Guo; V. V. Balagansky; N. V. Lubnina; Lifei Zhang (Геодинамика и тектонофизика)
Comparative analysis of the crustal evolution of the Early Precambrian Belomorian and Trans-North China orogens (Fig. 1) has shown [Slabunov et al., 2015] that: Both belts were formed by the superposition of two Precambrian orogenies. The earth crust of the Belomorian belt was produced during the Mesoarchaean to Neoarchaean Belomorian collisional orogeny [Slabunov, 2008; Slabunov et al., 2006] and then was reworked during the Palaeoproterozoic Lapland-Kola collisional orogeny [Daly at al., 2006; Balagansky et al., 2014]. The earth crust of the Trans-North China orogen was formed during a Neoarchean accretionary orogeny and then was reworked during a Paleoproterozoic collisional orogeny [Zhao et al., 2012; Guo et al., 2012, 2005]. The Lapland granulite belt is the core of the Lapland-Kola Palaeoproterozoic collisional orogen in the Fennoscandian shield and the Khondolite belt occupies the same tectonic position in a Palaeoproterozoic collisional orogen in the North China craton.